The Frailty Instrument for primary care of the Survey of Health, Ageing and Retirement in Europe predicts mortality similarly to a frailty index based on comprehensive geriatric assessment. - ROMERO-ORTUNO, ROMAN (My University, 2013)
AIM: Frailty is an emerging concept in primary care, which potentially can provide healthcare commissioners with a clinical focus for targeting resources at an aging population. However, primary care practitioners need valid instruments that are easy to use. With that purpose in mind, we created a Frailty Instrument (FIt) for primary care based on the Survey of Health, Aging and Retirement in Europe (SHARE). The aim of the present study was to compare the mortality prediction of the five-item SHARE-FIt with that of a 40-item Frailty Index (FIx) based on comprehensive geriatric assessment (CGA). METHODS: The participants were 15,578 women and 12,783 men from the first wave of SHARE. A correspondence analysis was used to assess the degree of agreement between phenotypic classifications. The ability of the continuous frailty measures (FIt score and FIx) to predict mortality (mean follow up of 2.4 years) was compared using receiver-operating characteristic (ROC) plots and areas under the curve (AUC). RESULTS: In both sexes, there was significant correspondence between phenotypic categories. The two continuous measures performed equally well as mortality predictors (women: AUC-FIx = 0.79, 95% CI 0.75-0.82, P < 0.001; AUC-FIt = 0.77, 95% CI 0.73-0.81, P < 0.001; men: AUC-FIx = 0.77, 95% CI 0.74-0.79, P < 0.001; AUC-FIt = 0.76, 95% CI 0.74-0.79, P < 0.001). Their equivalent performance was confirmed by statistical comparisons of the AUC. CONCLUSIONS: SHARE-FIt is simpler and more usable, and predicts mortality similarly to a more complex FIx based on CGA.
PUBLISHED
Keywords: CGA; CGA